2021
DOI: 10.1101/2021.03.08.434356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of coordinated muscular relaxation by a pattern-generating intersegmental circuit

Abstract: Typical patterned movements in animals are achieved through combinations of contraction and delayed relaxation of groups of muscles. However, how intersegmentally coordinated patterns of muscular relaxation are regulated by the neural circuits remain poorly understood. Here, we identify Canon, a class of higher-order premotor interneurons, that regulates muscular relaxation during backward locomotion of Drosophila larvae. Canon neurons are cholinergic interneurons present in each abdominal neuromere and show w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…C.4.B). It has been shown that several interneurons are activated in either forward or backward waves (Carreira-Rosario et al, 2018; Fushiki et al, 2016; Hiramoto et al, 2021; Kohsaka et al, 2019). In our data of pan-neuronal calcium recordings in the neuropil, such direction-specific activity could be observed only in the fine component (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C.4.B). It has been shown that several interneurons are activated in either forward or backward waves (Carreira-Rosario et al, 2018; Fushiki et al, 2016; Hiramoto et al, 2021; Kohsaka et al, 2019). In our data of pan-neuronal calcium recordings in the neuropil, such direction-specific activity could be observed only in the fine component (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted May 29, 2021. ; https://doi.org/10.1101/2021.05.28.445372 doi: bioRxiv preprint al., 2016; Hiramoto et al, 2021;Kohsaka et al, 2019). Accordingly, the decomposition step is critical to extract the proper activity of the neurons.…”
Section: Fine and Coarse Structure Decompositionmentioning
confidence: 99%